2015
DOI: 10.1016/j.phytochem.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Structure and cytotoxic activity of sesquiterpene glycoside esters from Calendula officinalis L.: Studies on the conformation of viridiflorol

Abstract: Topic applications of Calendula officinalis L. lipophilic extracts are used in phytotherapy to relieve skin inflammatory conditions whereas infusions are used as a remedy for gastric complaints. Such a different usage might be explained by some cytotoxicity of lipophilic extracts at gastric level but little is known about this. Therefore, we screened the CH2Cl2 extract from the flowers of C. officinalis by MTT and LDH assays in human epithelial gastric cells AGS. This bioassay-oriented approach led to the isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…However, internal use of lipophilic preparations from marigold flowers is not recommended for their renowned toxicity. In fact, our group has recently succeeded in identifying fractions and pure compounds which occur in the lipophilic extract from Calendula officinalis flowers and are toxic at the gastric level [ 28 ]. In the same work we demonstrated that the composition of lipophilic extract was not altered by gastric digestion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, internal use of lipophilic preparations from marigold flowers is not recommended for their renowned toxicity. In fact, our group has recently succeeded in identifying fractions and pure compounds which occur in the lipophilic extract from Calendula officinalis flowers and are toxic at the gastric level [ 28 ]. In the same work we demonstrated that the composition of lipophilic extract was not altered by gastric digestion.…”
Section: Resultsmentioning
confidence: 99%
“…Dry flowers of Calendula officinalis L. (variety Calypso Orange Florensis) were obtained and extracted as previously described [ 27 , 28 ]. A voucher specimen (number 20040929) is deposited at the Laboratory of Bioorganic Chemistry (Trento, Italy).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four Lipinski's properties molecular weight (MW), log P, hydrogen bond acceptor (HBA), and hydrogen bond donor (HBD) as well as two additional descriptors topological polar surface area (tPSA) and numbers of rotation bonds of compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) were calculated by Instant JChem version 17.10.0 from ChemAxon Ltd (Budapest, Hungary) of the molecules and projected onto a drug-like cut-off threshold of Lipinski's rules and Veber's oral bioavailability rule (Figure 8). Lipinski's rule of five, which considers orally active compounds and defines four simple physicochemical parameter ranges (MW ≤ 500, logP ≤ 5, HBD ≤ 5, and HBA ≤ 10) was combined with Veber's oral bioavailability rule, which includes two additional parameter ranges (tPSA ≤ 140 Å, number of rotatable bonds ≤10) [105,106].…”
Section: Rule Of Five and Veber's Oral Bioavailability Rule Of High Fmentioning
confidence: 99%
“…Recently, researchers have given priority to the use of medicinal plants for their contraceptive properties, with a majority of them being used as female contraceptive agents, while some affect the male reproductive system [2,3]. Albizzia lebbeck L. Benth (Mimosoidae), Anagallis arvensis L. (primulaceae), and Calendula officinalis L. (Astraceae) are annual plants containing oleanane saponins which have been linked to various biological activites affecting sperm [4][5][6]. A. lebbeck extracts have exhibited anti-inflammatory, antiallergic, and antidiabetic activities [7][8][9].…”
Section: Introductionmentioning
confidence: 99%